Patterns of Child Grooming and Sexual Harassment in Online Games - Gusnita, chazizah; Nurhadiyanto, Lucky; Ladiqi, Suyatno (Martabat: Jurnal Perempuan dan Anak, 2023)
The purpose of this study is to discuss patterns of child sexual abuse that occur in the online games Minecraft and Hago. The crime of child sexual abuse with the "Online Child Grooming" mode in online games is regarded as an effective method for child predators to lure potential victims. Grooming is a process in which a perpetrator approaches a person or organization gradually through communication relationships with the intent of sexually harassing them. Victims are typically children, adolescents, or adults who are at risk of becoming harassed. This study employs activity routine theory, which assesses the absence of capable guardian factors, motivated actors, and the presence of suitable targets, all of which, if they occur at the same time and place, make child grooming possible. The research was conducted descriptively and qualitatively.